Do rotational shear-cushioning shoes influence horizontal ground reaction forces and perceived comfort during basketball cutting maneuvers? - Lam,Wing-Kai; Qu,Yi; Yang,Fan; Cheung,Roy T.H. (PeerJ, 2017)
Background Court shoe designs predominantly focus on reducing excessive vertical ground reaction force, but shear force cushioning has received little attention in the basketball population. We aimed to examine the effect of a novel shoe-cushioning design on both resultant horizontal ground reaction forces and comfort perception during two basketball-specific cutting movements. Methods Fifteen university team basketball players performed lateral shuffling and 45-degree sidestep cutting at maximum effort in basketball shoes with and without the shear-cushioning system (SCS). Paired t-tests were used to examine the differences in kinetics and comfort perception between two shoes. Results SCS shoe allowed for larger rotational material deformation compared with control shoes, but no significant shoe differences were found in braking phase kinetics during both cutting movements (P = 0.35). Interestingly, a greater horizontal propulsion impulse was found with the SCS during 45-degree cutting (P < 0.05), when compared with the control. In addition, players wearing SCS shoes perceived better forefoot comfort (P = 0.012). During lateral shuffling, there were no significant differences in horizontal GRF and comfort perception between shoe conditions (P > 0.05). Discussion The application of a rotational shear-cushioning structure allowed for better forefoot comfort and enhanced propulsion performance in cutting, but did not influence the shear impact. Understanding horizontal ground reaction force information may be useful in designing footwear to prevent shear-related injuries in sport populations.
Keywords: Basketball shoe; Sidestep cutting; Lateral shuffling